STUDIES ON NATURAL PRODUCTS OF ALBIZIA SP. - HILMAN AFFANDI ARIFNURYADIN; HILMAN AFFANDI (SEAMEO BIOTROP, 1998)
The bark of Albizia lebeckioides and Albizia falcataria have been examined for their chemical constituents. A. lebeckioides has yielded the steroidal ketone, stigmasta-4,22-dien-3-one, and a triterpene alcohol as the major neutral components. A. falcataria has yielded a similar triterpene and fatty ester as its major constituents. The toxicity of the compounds was evaluated in bioassay against termites. The results showed that lupenone and stigmastadienone were toxic ioNeotermes dalbergiae species. In contrast these compounds were less toxic to Cryptotermes cynocephalus species. Key words: Insecticidal plants / Albizia lebeckioides I Albizia falcataria I Bark / Extracts / Chemical constituents / Toxicity / Termites